Color blind assistant app based on computer vision using openCV - Fahri Alfiansyah; Alfian Akbar Gozali; Akmal Natakusuma (Jurnal Mantik, 2023)
One of the health problems is color blindness. This disease is the inability to determine certain types of colors. The number of people with color blindness in Indonesia is increasing every year. Based on this problem, a color detection application was created to help color blind people based on computer vision. This application is made to be able to detect the color of objects in real-time using OpenCV library to detect color, taking objects using a smartphone camera. This application can detect an object moreover it can display color information in the form of sound from the smartphone. The color detection application aims to enhance the daily lives of color blind individuals especially in Indonesia by assisting them in perceiving and distinguishing colors in real-time, thereby promoting inclusivity and improving their overall experiences.